Detection of Helicobacter felis in a cat with gastric disease in laboratory animal facility - Hong, Sunhwa; Chung, Yungho; Kang, Won-Guk; Kim, Okjin (Laboratory animal research, 2016)
A 3-month-old male cat in the animal facility was presented for investigation of anorexia and occasional vomiting. We collected the specimens from gastroscopic biopsy and stool collection. The gastroscopic biopsy specimens were tested using a rapid urease test, CLO Helicobacter -detection kits. Stool specimens were gathered and evaluated using the commercially available SD Bioline H. pylori Ag kit according to the manufacturer’s instructions. Genomic DNAs from gastroscopic biopsy and stool specimens of the cat were extracted and submitted to the consensus PCR to amplify Helicobacter rpo B gene. Then the DNAs from gastroscopic biopsy and stool specimens were conducted a multiplex species-specific PCR to amplify urease B gene for H. heilmannii, H. pylori and H. felis . As the results, the rapid urease test with gastroscopic biopsy was revealed positive reaction. The result of H. pylori Stool Ag assay was one red line, negative for H. pylori . The gastroscopic biopsy and stool specimen were positive reactions by the consensus PCR reaction using the RNA polymerase beta-subunit-coding gene (rpoB) to detect Helicobacter species. By multiplex species-specific PCR with gastroscopic biopsy and stool specimens, no amplification products corresponding to either H. heilmannii or H. pylori were detected, but the specimens tested were positive for H. felis . This case was confirmed as gastroenteric disease induced by H. felis infection. On our knowledge, this is a very rare report about H. felis -induced gastroenteric disease in cat and may provide a valuable data on the study of feline Helicobacter infection.